Sifat Sensory dan Kimia pada Hard Candy dengan Penambahan Ekstrak Jagung Manis (Zea mays saccharata), Sukrosa Serta Madu : Sensory and Chemical Properties of Hard Candy with the Addition of Sweet Corn Extract (Zea mays saccharata), Sucrose, and Honey - Lia Amalia; Nabila Oktri Sumantri; Muhammad Rifqi Suryana (Universitas Djuanda, 2022)
Hard candy is a confection manufactured by melting a flavoring combination of glucose, fructose, and fruit juice. This research should focus on establishing the sensory properties of picked hard candy, including the fat and protein content, based on sensory quality. A fully randomized design (CRD) was utilized in this trial, with two factors: factor A was the concentration of sweet corn extract (100 g, 95 g, 90 g), while factor B was the concentration of sucrose and honey (60 g:10 g, 55 g: 15 g, 50 g: 20 g). The data were analyzed using ANOVA and Duncan's Advanced Test with a 95% confidence interval. The results showed that adding various concentrations of sweet corn extract, sucrose, and honey significantly affected the panelists' assessment of the sensory quality of color (brown-yellow to golden yellow) and texture (hard to very hard) in hard candy. The sensory quality of aroma (no smell of sweet corn to smell of sweet corn) and taste (sweet to very sweet) did not significantly affect the hard candy produced. Hard candy with the addition of sweet corn extract, sucrose, and honey selected is hard candy with A1B2 treatment (corn extract 100 grams, sucrose 55 grams, and honey 15 grams). The chemical testing showed that the selected hard candy product contained 1.11% fat and 2.06% protein content.